Principles of Forensic Audio Analysis - Maher, Robert C. (Modern Acoustics and Signal Processing,, 2018)
This book provides an expert introduction to audio forensics, an essential specialty in modern forensic science, equipping readers with the fundamental background necessary to understand and participate in this exciting and important field of study. Modern audio forensic analysis combines skills in digital signal processing, the physics of sound propagation, acoustical phonetics, audio engineering, and many other fields. Scientists and engineers who work in the field of audio forensics are called upon to address issues of authenticity, quality enhancement, and signal interpretation for audio evidence that is important to a criminal law enforcement investigation, an accident investigation board, or an official civil inquiry. Expertise in audio forensics has never been more important. In addition to routine recordings from emergency call centers and police radio dispatchers, inexpensive portable audio/video recording systems are now in widespread use. Forensic evidence from the scene of a civil or criminal incident increasingly involves dashboard recorders in police cars, vest-pocket personal recorders worn by law enforcement officers, smart phone recordings from bystanders, and security surveillance systems in public areas and businesses. Utilizing new research findings and both historical and contemporary casework examples, this book blends audio forensic theory and practice in an informative and readable manner suitable for any scientifically-literate reader. Extensive examples, supplementary material, and authoritative references are also included for those who are interested in delving deeper into the field. Outlines historical milestones in the field of audio forensics Features practical examples and recommendations Discusses research issues and challenges Includes practical guidelines for expert reports and testimony Covers digital audio signal processing for audio interpretation, intelligibility enhancement, and evaluation of authenticity.